Mental health and foster carer training. Issue 4 (1st April 2001) - Minnis, H; Pelosi, A J; Knapp, M; Dunn, J
Abstract : AIMS: To evaluate the impact of training foster carers on children's emotional and behavioural functioning. METHODS: In a randomised controlled trial in 17 Scottish local council areas, with immediate and nine month follow up, 182 children and their foster families were randomly allocated to either standard services alone or standard services plus extra training for foster carers on communication and attachment. Main outcome measures were child psychopathology, attachment disorder, self esteem, and cost of foster care. RESULTS: Over 60% of children had measurable psychopathology at baseline. The training was perceived as beneficial by participants. Scores for parent reported psychopathology and attachment disorders decreased by around 5%, self esteem increased by 2%, and costs by 22% in the intervention group. Results were non-significant. CONCLUSIONS: Despite being well received by foster carers, the training was not sufficient to make a useful impact on the high level of psychopathology. This group may warrant more intensive interventions.